Hubungan Perilaku Impulsif dan Stres Pengasuhan Terhadap Kecenderungan Nomophobia pada Remaja - Devi Monicca Sari; IGAA Noviekayati; Adnani Budi Utami (Jurnal Ilmu Sosial dan Humaniora, 2026)
Excessive smartphone use among adolescents has increased the risk of psychological problems, including nomophobia, which describes the feeling of anxiety or fear arising from the inability to access or utilize a smartphone. The purpose of this study was to examine the relationships between impulsive behavior and parenting stress with nomophobia among adolescents in Surabaya. A quantitative correlational design was employed involving 384 adolescents aged 13–18 years selected through purposive sampling. Data were collected using the Nomophobia Questionnaire (NMP-Q), Barratt Impulsiveness Scale (BIS-11), and Parenting Stress Scale, then analyzed using Spearman's rho correlation. The findings indicated a significant positive relationship between impulsive behavior and nomophobia (r = 0.225, p < 0.001) as well as between parenting stress and nomophobia (r = 0.148, p = 0.004). Most participants demonstrated moderate levels of impulsive behavior, parenting stress, and nomophobia. These findings indicate that impulsive behavior has a stronger association with nomophobia than parenting stress among adolescents